Islamic Character Education Model Forming Politeness in Muhammadiyah 3 Waru Junior High School - Hidayah Ummah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
AbstractFocus of this research is to describe the model of Islamic character education which is used as a basic form of politeness in Muhammadiyah 3 Waru Junior HighSchool. Character education curriculum needs to be embedded in a variety of character values and thoughts that can support students character as the next generation. This research method uses cooperative learning method. This research approach uses a qualitative approach. The results of this study are language politeness in Muhammadiyah 3 Waru Junior HighSchool influenced by Islamic character education models which has applied in the school environment. Keywords: Education Model, Character Education, Islamic Character, Politeness, Spoken Language, Cooperative Learning, Qualitative Reasearch..